2019
DOI: 10.1177/2050640618817699
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of chronic pancreatitis in pediatric population: Long‐term efficacy and safety

Abstract: Background: Chronic pancreatitis (CP) in children is an inreasingly recognized disease. Objective: The purpose of study was to analyse the safety and long-term efficacy of endoscopic treatment in children with CP. Methods: Records of 38 patients aged <18 years, referred to the Digestive Endoscopy Unit at Catholic University, Fondazione Policlinico ''A. Gemelli'' IRCCS between 1991 and 2017, were reviewed. Abdominal pain, analgesia and number of episodes of acute pancreatitis in the pre-and post-endoscopic retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Endoscopic treatment is recommended for CP starting at 8 years old under the same conditions as in adults [5]. Studies have shown over 50% pain resolution or improvement, decreased pancreatitis occurrence and decreased need for care after endoscopic treatment [15][16][17]. In our study, more than half of children who underwent ERCP for symptomatic CP had symptom relief during follow-up.…”
Section: Discussionmentioning
confidence: 59%
“…Endoscopic treatment is recommended for CP starting at 8 years old under the same conditions as in adults [5]. Studies have shown over 50% pain resolution or improvement, decreased pancreatitis occurrence and decreased need for care after endoscopic treatment [15][16][17]. In our study, more than half of children who underwent ERCP for symptomatic CP had symptom relief during follow-up.…”
Section: Discussionmentioning
confidence: 59%
“…In clinical application, propofol is characterized by a fast effect, short awakening time, and controllable anesthesia depth. However, it still has some disadvantages, such as large amounts of dosage and some adverse reactions, including obvious reduction in blood pressure, bradycardia, and apnea during deep sedation [ 32 ]. Liu et al [ 33 ] pointed out that the sedative effect of remimazolam benzenesulfonate was obviously better than that of midazolam during the diagnosis and treatment by colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the diversity of diseases classi cation and complexity of speci c therapeutic treatment, sex and age strati cation were not included in the study. Barakat et al [17] (2021) Asenov et al [19] (2019) Wen et al [20] (2019) [22] (2019)…”
Section: Study Characteristicsmentioning
confidence: 99%